The Turn-of-the-month Effect: Evidence From Macedonian Stock Exchange - Deari, Fitim; Ulu, Yasemin (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
We examine turn of the month effect for the Macedonian Stock Exchange using daily return data utilizing OLS and pooled regression analysis for the 10 components of the MBI10 index. We find that for most of the individual stock returns the coefficients of the turn-of-the-month effect are all positive indicating the presence of the turn-of-the-month effect. When the data is pooled, we obtain even stronger results. The study confirms that the turn-of-the-month effect holds for Macedonian Stock Exchange which has not been examined before. Therefore, on average, the daily return over the turn-of-the-month effect period is significantly higher than the daily return over the rest-of-the-month period and hence providing room for more investment opportunities.